1998
DOI: 10.1002/(sici)1097-4636(199811)42:2<245::aid-jbm9>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Surface topography can interfere with epithelial tissue migration

Abstract: Corneal epithelial tissue migration over the surface of a synthetic polymer can be inhibited by pores in the substrate. The effects of this substrate topography upon epithelial tissue migration were studied in vitro. Membranes of different porosities and structures were used to provide two series of surfaces having a graded increase in discontinuities: cellulose nitrate/acetate membranes with a tortuous network of pores, and track-etched polycarbonate membranes with columnar pores. Corneal epithelial tissue ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 39 publications
(26 reference statements)
3
57
3
Order By: Relevance
“…Substantial effects of substrate surface topography on cell shape, adhesion, and cell behavior have been reported in earlier studies [24][25][26]. The present findings indicate that the natural root surface topography appears to present a unique trigger for perpendicular cell elongation, ideally suited for periodontal fiber regeneration.…”
Section: Discussionsupporting
confidence: 77%
“…Substantial effects of substrate surface topography on cell shape, adhesion, and cell behavior have been reported in earlier studies [24][25][26]. The present findings indicate that the natural root surface topography appears to present a unique trigger for perpendicular cell elongation, ideally suited for periodontal fiber regeneration.…”
Section: Discussionsupporting
confidence: 77%
“…12 Years of protein deposition studies have revealed that it is not only the type of protein at the surface that is important for good cellular response but also the conformation of the protein and the ability of the cell to interact with it. [13][14][15][16][17][18] Extensive research on the cellular response to different proteins preadsorbed onto various surfaces, including collagen, 19,20 laminin, [21][22][23] vitronectin, 24,25 fibronectin, 14,26 and albumin, 27 indicate that synthetic materials must adsorb proteins in a relatively native conformation to improve their interaction with cells. 28 -30 If this can be accomplished, the material surface may interact with adhering cells in a manner similar to that of the native extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To that end, studies have used the matrix microstructure or nanostructure as key parameter to exercise precise control over cellular processes such as adhesion, migration, and function. [8][9][10][11][12][13] Recent mechanistic investigations suggest that substrate microtopography can alter the establishment and organization of cell membrane based focal adhesion complexes 14 and can thereby invoke specific signaling pathways which may regulate cellular phenotype and function. [15][16][17][18] Other studies have shown that the size of micropores on polymeric substrates can sensitively direct tissue epithelialization and migration upon polymer implantation.…”
Section: Introductionmentioning
confidence: 99%